FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES OF METOPROLOL SUCCINATE - Indresh (Journal of Biomedical and Pharmaceutical Research, 2021)
The anti-hypertensive transdermal patches in the perspective of enhancing the bioavailability as well as in improving patient compliance, it has appear as a substitute for oral route permit self-administration, controlled and sustained drug delivery. This study will investigate the effects of metoprolol Succinate in treatment of hypertension with the interaction of hydroxy propyl methyl cellulose and ethyl cellulose. The present research work concludes that the patches prepared with different ratios of polymers shows sustained drug release for long period of time confirms that the delivery system prepared can be suitably used as sustained and controlled drug delivery. The Transdermal Patches of drug metoprolol Succinate can be utilized in the diseases hypertension, myocardial infarction and congestive heart failure, etc. It offers high patient compliance by ease in administration.Keywords: Anti-hypertensive, Transdermal patches, Metoprolol succinate and HPMC.